2019
DOI: 10.1080/13691457.2019.1606787
|View full text |Cite
|
Sign up to set email alerts
|

‘If we want, they help us in any way’: how ‘unaccompanied refugee minors’ experience mentoring relationships

Abstract: View related articles View Crossmark data 'If we want, they help us in any way': how 'unaccompanied refugee minors' experience mentoring relationships

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
(34 reference statements)
0
15
0
3
Order By: Relevance
“…Several qualitative studies on asylum seekers in Sweden and Australia have underscored the culturally specific needs of mentees to feel safe and protected, the need for social support and social capital, and their strong desire to fit in and move forward with their lives [ 167 ]. Garraway and Pistrang [ 107 ], stressed the need to combine dyadic and group settings of mentoring among African-Caribbean young people, as the African-Caribbean culture values collectivism and community relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Several qualitative studies on asylum seekers in Sweden and Australia have underscored the culturally specific needs of mentees to feel safe and protected, the need for social support and social capital, and their strong desire to fit in and move forward with their lives [ 167 ]. Garraway and Pistrang [ 107 ], stressed the need to combine dyadic and group settings of mentoring among African-Caribbean young people, as the African-Caribbean culture values collectivism and community relationships.…”
Section: Resultsmentioning
confidence: 99%
“…During the programme, the mentors acted as agents for the empowerment of immigrant minors in a process through which the mentees acquired tools to gain autonomy in the new country and achieve life goals. In Europe, Raithelhuber [ 25 ] reached similar results and found that mentoring served as a springboard for the efficient integration of the youths participating in the study, unaccompanied refugees who, thanks to their mentors, saw their opportunities for civic participation increase. In the North American context, other studies corroborated both the more practical and instrumental effects of mentoring, such as learning the new language, improving academic performance or the acquisition of social skills [ 26 ], and the more emotional effects.…”
Section: Mentoring With Vulnerable Adolescentsmentioning
confidence: 79%
“…Some of these benefits involve an improvement in their emotional and cognitive skills, as well as better social development. The mentees that participated in the project, as has been observed in other participants of formal mentoring programmes aimed at the inclusion of young people of foreign origin [ 25 , 59 ], improved their access to social capital resources, whose social networks constitute the framework in which support exchanges take place. The perceived availability of social support reduced some symptoms of stress associated with the migration process and made the youths more resilient, despite enduring significant adversity.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, with unaccompanied migrant minors, other inquiries have stressed that mentoring encourages young migrants’ hope and feeling of belonging [ 60 ], as well as perceptions of the social support they have in the host culture [ 59 ]. This study further contributes to this field by shedding some light on the effects on unaccompanied youth once they turn 18, considering that our quantitative discoveries showed large effect sizes (‘d’ around 0.8) for the mentoring group on resilience (0.7), educational aspirations (0.86), and educational expectations (0.86), or medium effect sizes (‘d’ around 0.5) for self-esteem (0.54) and youth hope (0.45).…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as we know, there is no research showing the effects of mentoring on the mental health of unaccompanied migrant youths. What we know is that mentoring programmes can widen their social networks [ 59 ] and improve a sense of belonging and hope in the receiving society among migrant children living with their families in their new context [ 60 ].…”
Section: Introductionmentioning
confidence: 99%